INVENTARISASI SERANGGA PADA BERBAGAI JENIS VEGETASI LAHAN BERA PADI PASANG SURUT DI KABUPATEN INDRAGIRI HILIR - Yaherwandi, Hasmiandy hamid, Zahlul Ikhsan, Hidrayani, (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The agricultural ecosystem has a diversity of habitats that vary greatly from simple tocomplex. Observing the diversity of insects in agricultural areas is important to supportincreased production. An insect inventory study of tidal rice crops has been conducted inIndragiri Hilir Regency. Objective of research was to obtain information about the types ofinsects in tidal rice plant ecosystems. This research was conducted using purposiverandom sampling. Collection of insects was done using pitfall trap, yellow pan trap, swingnets and malaise traps. Tidal rice plantation area of Indragiri regency has 8 types of insectorder obtained from 4 types of traps installed, ie insect order diptera, hymenoptera,hemiptera, orthoptera, coleoptera, lepidoptera, collembola and odonata. The highestinsect population at the time before the rice planting period was occupied by insects of theorder, followed by hymenoptera, hemiptera, orthoptera, coleoptera, lepidotera, andcollembola respectively. Indragiri's downstream rice cultivation has high biodiversitypotential and biological agents to be developed.Kata kunci : Ecosystem, insect, habitat, tidal rice, malaise trap